Incineration bottom ash treatment through accelerated carbonation - Lin, Yvonne Wenlin (2016)
In Singapore, incineration is the main waste management technology used for handling municipal solid waste (MSW), in conjunction with recycling and other waste minimisation policy. After incineration, the volume of waste can be reduced up to 90%, thereby significantly reducing the demand of land space for the final disposal of waste. However, incineration cannot completely eradicate the need for landfill as the end product of incineration, i.e. incineration ash, still has to be disposed of properly in a sanitary landfill. Currently, Singapore’s only offshore landfill, Pulau Semakau, is estimated to last till 2035. With a lack of suitable alternative landfill in land scarce Singapore, there is an urgency to utilise incineration bottom ash (IBA), which accounts for 85-95% of the total residues produced after incineration, so as to prolong the lifespan of the landfill. Before IBA can be utilised, it has to be treated to reduce the leaching of heavy metals. This research proposes accelerated carbonation for IBA treatment as it has some advantages over other methods, and has not yet been explored in Singapore. Literature review has also shown this process is sustainable and economically viable. Before accelerated carbonation was carried out, the physical and chemical characteristics of untreated IBA were studied by collecting and analysing IBA from two incineration plants in Singapore, over a 6 months period. The two incineration plants, i.e. SWTEP and TSIP, were selected based on the types of waste received, which could then produce different mineralogical compositions of IBA. The 6 months sampling period was decided to cover the possible temporal variation of IBA characteristics. This characterisation study showed that the total element contents of IBA from both incineration plants in Singapore are similar to those in other countries reported in literature. However, elements like Cd, Co, Hg, Pb and Se exhibited high variation over the investigated sampling period. Pb showed similar high variation in leaching test. Lastly, Cu and Pb from both incineration plants did not meet the criteria for watercourse discharge while F- from SWTEP did not meet the sewer criteria, if no treatment was carried out. This 6 months study has found Pb to be a potential problem in the utilisation of IBA due to its high variation. The accelerated carbonation experiment was divided into two parts. In the first part, the influence of moisture content and temperature on accelerated carbonation was investigated using the 0-2 mm size fraction of IBA. The optimum operating conditions found in the first part was then applied to other size fractions (i.e. 2-4 mm, 4-20 mm and 20-50 mm) in the second part of the experiment. Results showed that the optimum operating conditions fixed at 20% CO2 at 1 atm for the two incineration plants were slightly different. For SWTEP, it was 35C and 15% moisture content. For TSIP, it was 50C and 15% moisture content. The carbonation duration for both plants was 2 hours. XRD analysis showed slight difference between the mineralogical compositions of the two incineration plants, which could explain the different optimum carbonation temperatures. Most of the heavy metals (i.e. Pb, Zn, Cu and Cr) were found to reduce in leaching after accelerated carbonation, whereas Mo and Sb leaching generally increased after carbonation. After sieving the IBA into four different size fractions, the amount of soluble salts released from untreated IBA showed decrement as the size increased. The leaching mechanism among the different size fractions was found to be similar. Despite the limitations in reducing the leaching of certain trace elements (i.e. Mo and Sb), accelerated carbonation was able to significantly reduce the amount released of Pb, Zn, Cu and Cr. On the other hand, accelerated carbonation was found to be ineffective in reducing the leaching of soluble salts. This study showed that the increase in calcite after carbonation was not the direct contributor to the reduction in leaching. Rather, the effect of carbonation resulted in the decrease in pH and the formation of secondary minerals, which then contributed to the reduction in leaching through solubility control and adsorption. Lastly, the difference in mineral content in the different size fractions gave rise to varying percentage of reduction in leaching after carbonation. In conclusion, this study has shown that accelerated carbonation has the potential to treat IBA effectively within a short time frame.